Impacts of the new improbity law on public administration (Research, Society and Development, 2023)
This article aims to carry out a literature review on the impacts of the new improbity law (Law No. 14,230 of 2021) on public administration. Therefore, it is a study of the type Integrative Literature Review. Some of the changes brought about by the recent reform in the administrative impropriety legislation include the requirement of proof of intent for punishment, the sanctioning of private entities that have received state benefits, the elimination of the loss of office/mandate in some infractions, the restriction of the sanctioning of third parties and the creation of a specific legal action for cases of impropriety, instead of applying the public civil action. In addition, the Public Prosecutor's Office gains private standing to file actions of impropriety and the requirements for filing the action become more rigorous, with the need to qualify the facts. However, it is important to note that these changes may result in a weakening of the State's punitive power, which may have harmful consequences for society. It is concluded that the legislator showed, in the elaboration of this legislative alteration, that he is little interested in the social desire and is not concerned with the public interest, since the negative impacts on society could be immense, since the promotion of deviation from public morality gained new place in the legislation.